# Find sinx2, cosx2, and tanx2 from the given information.sin(x) = 513, 0° < x < 90°

## Related Questions

The opposite side, y, is the height of the dam less 1.65 m

The base or adjacent side is 90 m

The angle between the two sides is 90 m.

Then tan (26) = y / 90

y = 90 tan(26) = 90 (0.4877) = 43.90 m

The height of the dam is 43.90m + 1.65m = 45.55 m

For f(x)=2x+1 and g(x)=x^2-7, find (f-g)(x)

(f-g)(x)=2x+1-(x^2-7)

(f-g)(x)=2x+1-x^2+7

(f-g)(x)= -x^2+2x+8

9x² - 36x + 36 = 0

9(x² - 4x + 4) = 0

9(x-2)(x-2) = 0

Radicand = Discriminant = 36² - 4(9)(36) = 0

there is 1 real zero that repeats itself)

zero is x=2.

Use factoring. Factors of 7 are 1 and 7

2x²-9x+7 = 0

(2x-7)(x-1) = 0

2x-7 = 0 (x-1)=0

2x = 7x=1

x = 7/2

Your solutions are x = 1 and x = 7/2

I hope my answers helped you

TopAcademicTutors.Com

Expert Assignment Help for students who have pending assignments.

For 10$ a page, you can get your written essay.

p = take home pay

r = rate of dollars per hour

h = number of hours worked

b = bonus

So now we can find h and let us start with the formula.

p = 0.7(rh + b)

p = 0.7*r*h + 0.7b

p - 0.7b = 0.7rh

So the answer for this problem is

**h = (p-0.7b)/0.7r**

1. C

2. A, C

3. B

4. C

5.

[Part 1]

A

[Part 2]

C

6. D

7.

[Part 1]

B

[Part 2]

A

[Part 3]

C

100% Correct

**Answer with explanation:**

In a triangle sum of two sides , should always be greater than the third side.

Sides of the given triangle are, 3 x cm, 7 x cm and h cm.

1.

3 x + 7 x > h

**→ 10 x > h**

2.

3 x+ h > 7 x

→h > 7 x -3 x

**→h> 4 x**

3.

7 x + h > 3 x, which will be always true.

Combining 1, 2 and 3 we get

**→4 x < h < 10 x**

**Option A**

TopAcademicTutors.Com

Expert Assignment Help for students who have pending assignments.

For 10$ a page, you can get your written essay.

What is f(x) = 2x2 + 28x – 5 written in vertex form?

f(x) = 2x^2 + 28x – 5

f(x) = 2(x^2 + 14x) – 5

f(x) = 2(x^2 + 14x + 49) – 5 - 98

**f(x) = 2(x + 7)^2 – 103**

Hope this answers the question. Have a nice day.

Given f(x)=17-x^2, what is the average rate of change in f(x) over the interval [1, 5]?

average rate of change is

(f(5) - f(1))/(5 - 1) =

(17 - 5^2 - (17 - 1^2))/4 =

(17 - 25 - 17 + 1)/4 =

So the answer for this problem is

**-6**

I hope my answer helped you. Feel free to ask for more questions.

TopAcademicTutors.Com

Expert Assignment Help for students who have pending assignments.

For 10$ a page, you can get your written essay.

Line Segment

E) part of a line that has two endpoints

Plane

D) a flat surface that extends infinitely and has no thickness

Perpendicular Lines

B) two lines that intersect at 90° angles

Line

A) a series of points that extend in two directions without end

Parallel Lines

C) lines that lie in the same plane and do not intersect

Hope this answers the question. Have a nice day.

-x = 1.5x – 4

4 = 2.5x

**x = 1.6**

y = -x = -1.6

y = -x = -1.6

f(x) = P(1 + r)^x

Now we can solve.

Given:

P = 2000

r = -0.06

f(x) = 2000 (1 - 0.06)^x

= 2000 (0.94)^x

2000 (0.94)¹² =

2000 (0.476) =

The answer is

**951.8 square kilometers.**

TopAcademicTutors.Com

Expert Assignment Help for students who have pending assignments.

For 10$ a page, you can get your written essay.

**The answer is**

BThe vertex of the graph is (5, –37).

B

**The parabola has a minimum.**

C

C

**D**The parabola opens up.

If the equilibrium interest rate in the money market is 5%, then at an interest rate of 2% sellers of interest-bearing financial assets greater than interest rates to find willing buyers.

Which ordered pair is a solution of the equation 2x − y = 9 (-4,1) (-2,5) (5,1) (6,-3)

So based on my solution, the correct answer would be the third option: (5,1)

So let us try to plug in the values.

2(5) - 1 = 9

10 -1 = 9

9 = 9

So this is the correct one. Hope this answers your question.

TopAcademicTutors.Com

Expert Assignment Help for students who have pending assignments.

For 10$ a page, you can get your written essay.

What is the range of the function f(x) = 3x2 + 6x – 9

f(x)=3x^2-6x+1

My solution is:

The domain is all real numbers--there are no restrictions like a square root or variable in the denominator

this is a U shape parabola and you want to find the bottom point, it is at the vertex

x=-b/2a =- (-6) /2 (3) =1

f(1) =3(1)^2 -6(1) +1 =3-6+1 =-2

the minimum is (1, -2)

so the range is all real numbers >= -2

By examining my solution, you could just answer the problem on your own! I hope it helps!

Find the multiplicative inverse of 6 + 2i.

First thing to do is get rid of the i. Multiplying by 6 - 2i will do this

( 6 + 2i)(6 - 2i) = 6^2 - (2i)^2 = 36 - 4(-1) = 36 + 4 = 40

Dividing by 40 gets you 1

(6 + 2i) (6-2i)/40 = 1

**The answer is (6 - 2i)/40 = (3 - i)/20**

I hope my answer has come to your help. God bless and have a nice day ahead!

Solve the equation for y 2x+6y=13

2x+6y=13

Next, transfer 2x to the right side and it will look like this:

6y=13-2x

Now, divide both sides by 6, and it will look like this:

y=13-2x

--------

6

So, this is the final answer for y.

Hope this answers your question. Have a great day!

TopAcademicTutors.Com

Expert Assignment Help for students who have pending assignments.

For 10$ a page, you can get your written essay.

How to solve this problem 14-6= 10-6=?

Algebraic terms are separated by ______. Choose all that apply. 1)= 2)+ 3)x 4)÷ 5)-

__Answer__

1)=

2)+

5)-

__Explanation__

When letter or numbers are separated by multiplication or division can be combined to make one term.

In an algebra equation, terms are separated by an addition sign, subtraction sign or an equal sign. For example,

3a + 7b = 21.

This equation have 3 terms.

TopAcademicTutors.Com

Expert Assignment Help for students who have pending assignments.

For 10$ a page, you can get your written essay.

**If ST = 21, SP = 3b – 11, and PT = b + 4, the value of b would be 14.**

I hope my answer has come to your help. God bless and have a nice day ahead!

is as follows

mean=13(.5)=6.5

variance=6.5(.5)=3.25

Pr[fewer than 4]=

Pr[N<=3] Apply the continuity correction

Pr[N<=3.5]~=Pr[Z<3.5-6.5/sqrt(3.25)]=

Pr[Z<-1.66]=0.048457226

I hope my answer has come to your help. God bless and have a nice day ahead!

6 times the square root of 2.25 and then minis 4.23 =

________________

6√(2.25) - 4.23 = ?

__________________

6√(2.25) - 4.23 =

______________________

6*(1.5) - 4.23 =

_______________

9 - 4.23 =

_______________

4.77

TopAcademicTutors.Com

Expert Assignment Help for students who have pending assignments.

For 10$ a page, you can get your written essay.

90/3 : (2 1/2)/3

30 : (2 1/2)/3

30 : (5/2)/(3/1)

30 : 5/2*1/3

30 : 5/6

30km in 50 mins

90 : 2 1/2

90/(2 1/2) : (2 1/2) / (2 1/2)

90/(2 1/2) : 1

(90/1)/(5/2) : 1

(90/1)*(2/5) : 1

180/5 :1

36:1

Multiply each side by 2:

72:2

72 km in 2 hours

Hope this helps :)

**Answer: The correct option is (A) b < 4000.**

**Step-by-step explanation: **Given that the public library has fewer than 4,000 books.

We are to select the** inequality that describes the number of books in the library.**

The number of books in the library is represented by b.

According to the given information, the **inequality hat describes the number of books in the library is given by**

**Thus, (A) is the correct option.**

TopAcademicTutors.Com

Expert Assignment Help for students who have pending assignments.

For 10$ a page, you can get your written essay.

**Answer:**

**C.$ 623**

**Step-by-step explanation:**

We are given that Sophia is saving money for a new bicycle.

The bicycle will cost atleast $623.

Sophia makes $8.22 per hour.

We have to find the inequality that could be used to find the number of hours Sophia needs to work to make enough money to buy a new bicycle.

Let Sophia works h hours to make enough money to buy a new bicycle.

Sophia makes money per hour =$8.22

Total money made by Sophia in h hours =

According to question

**$623**

**Hence, option C is true.**

Solve the inequality. p – 9 < –9

p-9 < -9

p-9+9 < -9+9

p <0

**1) The answer is: [B]: r = 5 .**

**__________________________**

**Explanation:**

**___________**_______________

Given: 7r − 7 = 2r + 18 ; Round your answer to the nearest tenth, if necessary.

____________________________

Since "r" is the only variable given, let us assume we want to solve for "r" (instead of "x").

___________________________

→ Subtract "2r" from EACH SIDE of the equation; and & add "7" to EACH SIDE of the equation:

_____________

→ 7r − 7 − 2r + 7 = 2r + 18 − 2r + 7 ; to get: → 5r = 25 ;

_____________

→ Now, divide EACH SIDE of the equation by "5"; to isolate "r" on one side of the equation; and to solve for "r" :

______________

→ 5r / 5 = 25 / 5 → r = 5 → which is: "Answer choice: [B]".

_________________

**Let us check our answer, by plugging in "5" for "r" in the original equation:**

_________________

→ 7r − 7 = 2r + 18 ; → 7(5) − 7 =? 2(5) + 18? ;

______________________

→ 35 − 7 =? 10 + 18 ?; → 28 =? 28? Yes!

______________________

**2) The answer is: [D]: x = 2 .**

**_____________**

**Explanation:**

_____________

Given: 2x + 12 = 18 − x ; Solve for "x" (round to nearest tenth, if necessary).

_______________

→ Add "x" to EACH SIDE of the equation, & subtract "12" from EACH SIDE of the equation: → 2x + 12 + x − 12 = 18 − x + x − 12 ;

______________

→ To get: 3x = 6 ; → Divide EACH SIDE of the equation by "3";

to isolate "x" on one side of the equation; and to solve for "x":

_____________

→ 3x / 3 = 6 / 3 ; → x = 2 ; which is: "Answer choice: [D]".

______________

**Let us check our answer, by plugging in "2" for "x" in the original equation:**

________________

→ 2x + 12 = 18 − x ; → 2(2) + 12 =? 18 − 2 ?

________________

→ 4 + 12 =? 18 − 2 ? ; → 16 =? 16? Yes!

________________________________

**3) The answer is: [A]: x = -3 .**

**_____________**

**Explanation:**

________________

Given: 8x − 3 = 15x + 18 ; Solve for "x". Round your answer to the nearest tenth, if necessary.

_________________

→ Subtract "8x" from EACH SIDE of the equation, & add "3" to EACH SIDE of the equation:

_______________

→ 8x − 3 − 8x + 3 = 15x + 18 − 8x + 3 ; to get:

_______________

→ 0 = 7x + 21 ; → Subtract "21" from EACH SIDE of the equation;

_______________

→ 0 − 21 = 7x + 21 − 21 ; to get:

_______________

→ -21 = 7x ; Now divide EACH SIDE of the equation by "7";

to isolate "x" on one side of the equation; & to solve for "x":

_______________

→ = -21 / 7 = 7x / 7 ; → -3 = x ; which is "Answer choice: [A]."

**_________________**

**Let us check our answer, by plugging in "-3" for "x" in the original equation:**

________________

→ 8x − 3 = 15x + 18 ; → 8(-3) − 3 =? 15(-3) + 18 ?;

________________________

→ -24 − 3 =? -45 + 18 ? ; → -27 =? -27? Yes!

**___________________________**

**4) The answer is: [C]: y = 11 .**

**_____________**

**Explanation:**

**____________**

Given: 6y − 6 = 4y + 16 ; Solve for "y"; Round to the nearest tenth, if necessary.

____________

(Note: Since "y" is the only variable given; assume we are to solve for "y" instead of "x").

____________

→ Subtract "4y" from EACH SIDE of the equation, & add "6" to EACH SIDE of the equation; → 6y − 6 − 4y + 6 = 4y + 16 − 4y + 6 ; to get:

_______________

→ 2y = 22 ; Now, divide EACH SIDE of the equation by "2"; to isolate "y" one side of the equation; and to solve for "y" ;

_______________

→ 2y / 2 = 22 / 2 ; → y = 11 → which is "Answer choice: [C]".

**_______________________________**

**Let us check our answer, by plugging in "11" for "y" in the original equation:**

**___________________**

→ 6y − 6 = 4y + 16 ; → 6(11) − 6 =? 4(11) + 16 ?

_______________________

→ 66 − 6 =? 44 + 16 ? → 60 =? 60 ? Yes!

**__________________**

**5) The answer is: [B]: x = -11 .**

**_____________________**

**Explanation:**

**_________________**

Given: 3(x − 4) = 5(x + 2) ; Solve for "x". Round to the nearest tenth, if necessary.

**___________**

**→Note the "distributive property of multiplication":**

**_____________**

**a*(b + c) = ab + ac ; and: a*(b − c) = ab − ac ;**

**_______________**

→ Let us expand EACH SIDE of our given equation.

→Start with the "left-hand side":

____________

3(x − 4) = (3*x) − (3*4) = 3x − 12;

______________________________

→Now let us expand the "right-hand side" of the given equation:

____________

→ 5(x + 2) = (5*x) + (5*2) = 5x + 10 ;

______________

→Now, we can rewrite the original equation:

_______________

→ 3(x − 4) = 5(x + 2) ; by substituting the expanded values for EACH SIDE of the question: → 3x − 12 = 5x + 10 ;

__________________

→ Subtract "3x" from EACH SIDE of the equation; and add "12" to EACH SIDE of the equation: → 3x − 12 − 3x + 12 = 5x + 10 − 3x + 12 ; to get:

________________

→ 0 = 2x + 22; → Now subtract "22" from EACH SIDE of the equation:

______________

→ 0 − 22 = 2x + 22 − 22 ; to get: → -22 = 2x ;

__________

→ Divide EACH SIDE of the equation by "2"; to isolate "x" on one side of the equation; & to solve for "x" ;

_____________

→ -22 / 2 = 2x /2 ; → -11 = x ; which is "Answer choice: [B]".

______________

**Let us check our answer, by plugging in "-11" for "x" in the original equation:**

**___________**

→ 3(x − 4) = 5(x + 2) ; → 3(-11 − 4) =? 5(-11 + 2) ? ;

_______________________

→3(-15) =? 5(-9) ? ; → -45 =? -45 ? Yes!

**_____________________________________________**

**Hope these answers and explanations are helpful. Best of luck!**

TopAcademicTutors.Com

Expert Assignment Help for students who have pending assignments.

For 10$ a page, you can get your written essay.